Wealth-based inequalities in early childhood development (ECD) outcomes in Bangladesh: A decomposition analysis using MICS 2019. - Tasfia Tasneem Ahmed; Nafis Sadik (PLOS Global Public Health, 2025)
Early Childhood Development (ECD) inequality among different socioeconomic groups is a rising concern in developing countries. This paper aimed to identify and decompose the ECD inequality among poor and non-poor groups in Bangladesh. For measuring inequality in ECD, concentration curves and their corresponding indices were used in this study utilizing the Multiple Indicator Cluster Survey 2019 data. Furthermore, a standard decomposition approach has been used to decompose the inequality. Findings reveal that children from poor families consistently exhibit lower scores across all ECD domains. Notably, a significant disparity exists in the literacy-numeracy domain, with a concentration index of 0.1825. A lower proportion of poor children (34.17%) meet developmental milestones compared to their well-off counterparts (65.83%). Key determinants influencing ECD outcomes among the poor group include attendance at early childhood education (ECE) programs, sex of the child, multiple childcare involvement of mother, and supervision quality. Additionally, wealth-based disparities in ECD outcomes can be attributed to factors such as maternal education, access to books, nutrition, and the quality of childcare provided. The findings underscore the urgent need for targeted interventions and policy reforms aimed at addressing the specific needs of disadvantaged children, especially for literacy and numeracy skills. By prioritizing poverty reduction initiatives, access to quality Early Childhood Education (ECE) programs, provision of books, improving maternal education, and enhancing supervision quality, efforts can be made to narrow the wealth-based gap in ECD.